Neighborhood deprivation and physical activity facilities: no support for the deprivation amplification hypothesis - Schneider, Sven; Diehl, Katharina (Journal of physical activity and health, 2015)
Background: The “deprivation amplification” hypothesis states that individuals who are already socially disadvantaged experience a further contextual disadvantage regarding their access to health relevant facilities. This hypothesis is investigated for the first time for Germany, led by the question as to whether deprived neighborhoods experience worse access to physical activity facilities than affluent ones. We differentiate between facilities for children and adolescents vs. for adults, and between free vs. fee-based facilities. Methods: We identified all physical activity facilities by traversing each neighborhood by foot or bicycle in the framework of a systematic audit. Number, location, and type of facilities were recorded and visualized. The investigation area encompassed 18 social areas in a major German city with 92,000 inhabitants and an area of 12.0 km2. Results: A lower socioeconomic area status was related to a higher availability of physical activity facilities for children and adolescents (7.11/1000 minors in deprived social areas versus 4.46/1000 minors in affluent social areas; P < .05). For adults, the pattern was similar but not significant (P ≥ .05). These results were also shown in analyses in which only free facilities were taken into consideration. Conclusions: Our study cannot support the “deprivation amplification” hypothesis regarding the availability of physical activity facilities.